(3GdOQQ GdMSGf aj Md eTcd bhdg JYGdi (B"(3GdBf(B"s - (3Ydj Hf eMSf GdUYjOj GdhaGFj GdQejdj, CHh GdUdGM,J (B1130 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd GdYHO GdabjQ Edi QMeI QHg CHhGdUdGM GdCRgQj SCdfj HYV ENhGfj Cf CLeY QSGdI aj HYV eTcdGJ s
(3BNQgG (B:s
(3hdLejY GdeSdejf hdef bQC aj gPg GdQSGdI hOYG HGdeZaQI hUdi Gddg Ydi SjOfG eMeO hYdi Bdg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B323 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B175s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B465s
(3eUOQ GbJfGA GdCUd (B:s
(3GdCRgQ s
Keywords: (3GdbQGAGJ hGdJLhjOs